BUDAYA ORGANISASI DAN KINERJA PEGAWAI (STUDI PADA DINAS PEMUDA OLAHRAGA PARIWISATA DAN KEBUDAYAAN KABUPATEN PROBOLINGGO) - Prihan Suhudi; Rosidi; Jamal Abdul Naser (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2022)
Employee performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Based on this, this research study aims to determine the application of organizational culture and employee performance at the Department of Youth, Sports, Tourism and Culture of Probolinggo Regency. This study uses a qualitative method. Qualitative research is a scientific research, which aims to understand a phenomenon in a natural social context by prioritizing the process of deep communication interaction between researchers and the phenomenon under study. Researchers took the research location with observations at the Youth, Sports, Tourism and Culture Office of Probolinggo Regency to support the data needed in research related to the application of organizational culture and employee performance. Sources of data obtained from the field where the research was carried out. To obtain this data, the interview method was used. This data was obtained from the results of the answers of related informants. The results of this study are as follows: (1) Organizational Culture at the Department of Youth, Sports, Tourism and Culture of Probolinggo Regency is in the good category, because it can increase motivation and can form good attitudes and behavior in employees. (2) Employee performance at the Probolinggo Regency Youth, Sports, Tourism and Culture Office is also in the good category, meaning that the employee's performance has carried out their duties well, is responsible for work, prioritizes work and manages time well.